Legal Conflict in Zakat Management in the Prismatic Communities of Kapuas Regency, Central of Kalimantan - Masrawan, Masrawan; Anshari, A. Hafiz; Hakim, Budi Rahmat; Syaikhu, Syaikhu (Universitas Islam Negeri Raden Intan Lampung, 2022)
Abstract: Legal Conflict in Zakat Management in the Prismatic Communities of Kapuas Regency, Central of Kalimantan. This study is aimed at analyzing the legal conflict in the management of zakat (charity) among prismatic communities in Kapuas Regency, Central of Kalimantan. This intersection occurs between Islamic law relating to the management of zakat and the tradition, or customary law held by the local community. This phenomenon gives rise to poly normativism (legal overlap) between formal rules and living traditions in the local community. This research is empirical-normative in nature, using a combination of several approaches, i.e., the empirical, historical, normative, and conceptual approaches. The data were obtained through interviews, documentation, and direct observation of zakat management institutions and community behavior supported by the tradition of local society. The results of the study indicate that there is an intersection between the rules used in the management of zakat and the customary laws that live in a prismatic society in Kapuas Regency. For this reason, it is necessary to make adjustments in the regulation of zakat management while raising public awareness of the importance of optimizing zakat to support the interests of the state, in general, and in particular, for the interests of the local Muslims themselves.